Perilaku Nasabah Dalam Pengelolaan Modal Usaha Permodalan Nasional Madani (PNM Mekaar) Menurut Persfektif Ekonomi Islam Di Kecamatan Jelutung Kota Jambi - Rosalinda, Melisa; Orinaldi, Mohammad; Safitri, Yuliana (STAI Denpasar Bali, 2023)
This study aims to find out how the behavior of Mekaar PNM customers in Jelutung, the number of informants in this study were 3 informants, namely the branch head, account officer, and Mekaar jelutung PNM customers. The type of this research is descriptive qualitative with primary data and secondary data. Data collection techniques in this study used observation, documentation and interview techniques, while for data analysis the researchers used data reduction, data presentation and verification. The results of this study explain the behavior of PNM Mekaar's customers, there are two indicators of customer behavior, namely production and consumption where managing capital is more productive or developing to maintain a business so it doesn't run out in vain.